Simultaneous sorption of four ionizable pharmaceuticals in different horizons of three soil types - Kočárek, Martin; Kodešová, Radka; Vondráčková, Lenka; Golovko, Oksana; Fér, Miroslav; Klement, Aleš; Nikodem, Antonín; Jakšík, Ondřej; Grabic, Roman (Environmental pollution (Barking, Essex, 2016)
Soils may be contaminated by human or veterinary pharmaceuticals. Their behaviour in soil environment is largely controlled by sorption of different compounds in a soil solution onto soil constituents. Here we studied the sorption affinities of 4 pharmaceuticals (atenolol, trimethoprim, carbamazepine and sulfamethoxazole) applied in solute mixtures to soils taken from different horizons of 3 soil types (Greyic Phaeozem on loess, Haplic Luvisol on loess and Haplic Cambisol on gneiss). In the case of the carbamazepine (neutral form) and sulfamethoxazole (partly negatively charged and neutral), sorption affinity of compounds decreased with soil depth, i.e. decreased with soil organic matter content. On the other hand, in the case of atenolol (positively charged) and trimethoprim (partly positively charged and neutral) compound sorption affinity was not depth dependent. Compound sorption affinities in the four-solute systems were compared with those experimentally assessed in topsoils, and were estimated using the pedotransfer rules proposed in our previous study for single-solute systems. While sorption affinities of trimethoprim and carbamazepine in topsoils decreased slightly, sorption affinity of sulfamethoxazole increased. Decreases in sorption of the two compounds could be attributed to their competition between each other and competition with atenolol. Differences between carbamazepine and atenolol behaviour in the one- and four-solute systems could also be explained by the slightly different soil properties in this and our previous study. A great increase of sulfamethoxazole sorption in the Greyic Phaeozem and Haplic Luvisol was observed, which was attributed to elimination of repulsion between negatively charged molecules and particle surfaces due to cation sorption (atenolol and trimethoprim) on soil particles. Thus, our results proved not only an antagonistic but also a synergic affect of differently charged organic molecules on their sorption to soil constituents.
Keywords: léčivé přípravky; Adsorption; karbamazepin; ionty; Trimethoprim; látky znečišťující půdu; Atenolol; Ions; Soil Pollutants; atenolol; sulfamethoxazol; trimethoprim; půda; Carbamazepine; Soil; Sulfamethoxazole; Pharmaceutical Preparations; adsorpce